Human Right for Fair Wage: sociological aspect - Tatiana Mihailovna Ponomareva; Eleonora Aleksandrovna Kalyuga (Сибирское юридическое обозрение, 2012)
The article summarizes the results of sociological research devoted to the analysis of the fair wage problem. The authors analyze the dynamics of labor load and the level of wages in the economic market conditions taking as an example the Omsk Region.